(untitled) (Revista Iberoamericana de Bioética, 2024)
This paper discusses the importance of respecting human rights in the context of palliative care, particularly for elderly patients who are more commonly affected by chronic and incurable diseases and often require such care. It highlights the need for the adequate promotion of palliative care in light of the world’s aging population. These rights ensure the well-being and quality of life of elderly patients receiving palliative care. They include the right to health, which guarantees access to palliative care, as well as the right to privacy, freedom from torture or cruel, inhuman or degrading treatment or punishment, freedom from discrimination, and the right to information. This is theoretical and normative research based on the Human Rights of Patients framework. It concludes that training in human rights for healthcare professionals and the legal provision of patient rights are essential.